GEOMETRY OF MYOCARDIUM SHAREWARE HEALTHY TEENAGE BOYS BEFORE JOINING THE ARMY AGE - Елена Владимировна Пшеничная (The Publishing House Medicine and Enlightenment, 2017)
547 adolescent boys aged 15-16 years were examined. He was given a standard ECG, a 24-hour Holter ECG monitoring, Doppler echocardiography. Pathological forms of myocardium geometry were revealed in 52 (9,5 ± 1,3 %) of the examined: 36 (69,2 ± 6,4 %) of adolescents had concentric hypertrophy, 16 (30,8 ± 6,4 %) - concentric remodeling. Eccentric hypertrophy of the left ventricle was not diagnosed in the adolescent boys surveyed. The pathological geometry of the left ventricle in all cases was accompanied by diastolic dysfunction. At the same time, the ejection fraction in all individuals remained within the limits of normal values. Small structural abnormalities in the heart were found in 161 adolescents (83,9 ± 2,7 %). This was the basis for changing the regime and intensity of physical activity, the appointment of corrective therapy.